Study of Students’ Perception Regarding Open Book Assessment and Closed Book Exams - Dayananda R1 , Mahantesh Patil2, Manjunath S N3 , Rajapur Parshuram4 , Vijay Kautilya5 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background - An “open book examination” is one in which students are allowed to refer to their notes,textbooks, and other approved material while answering questions. This practice is mostly unheard of. It isideally suited to professional courses like MBBS which especially aim at developing the skills of criticaland creative thinking.Materials and Methods – After a lecture on chapter Medical Law and ethics 100 students selected throughsimple random sampling after obtaining informed consent were given Pre test. Then they were divided into2 groups. The topic Medical Law and Ethics was divided into 2 Parts. The students of Group 1 undertookopen book exams for Part A and Self study exams for Part B and for students of Group 2 it was reversed.Post test was done with the validated pretest questions. To check the retention another open book examwas performed after a month. The students also answered a questionnaire on their perception of open bookexams and the reason for their preferences and it was analyzed.Conclusion – A total of 100 students participated in the study. In that 60 were medium achievers and 40were high achievers. Both medium achievers and high achievers obtained high scores in open book exams.Most of the students felt that Open book exam is less time-consuming for preparation, less stressful andincreased their Self-directed learning. Open book exams is better to the closed book exams and inculcatesthe habit of life-long learners.